2021
DOI: 10.1002/2688-8319.12053
|View full text |Cite
|
Sign up to set email alerts
|

LED lighting threatens adult aquatic insects: Impact magnitude and distance thresholds

Abstract: 1. Artificial light at night (ALAN) is increasing globally, and changing in quality due to the installation of white LED street lighting. ALAN is a threat to biodiversity and ecosystem functioning, yet important knowledge gaps exist regarding the magnitude of impacts and how these vary between habitats and levels of exposure. TheThis is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(141 reference statements)
1
5
0
Order By: Relevance
“…With autochthonous proportional abundance greater in the littoral zone and allochthonous proportional abundance greater in the riparian, there is evidence that short-wavelength LED lighting creates both dispersal barriers and an asymmetrical vacuum effect wherein aquatic emergent insects are more readily pulled from their habitat of origin than are terrestrial invertebrates. A recent study examining distance thresholds on adult aquatic insects [48] found that a majority of Trichoptera were captured much closer to the aquatic-riparian border than other taxa, such as Ephemeroptera, concurring with our findings that the capture versus vacuum effect varies among taxa. This taxa-specific response suggests a degree of predictability of communities and ecosystems to ALAN, and also highlights the context dependency of our work, performed in a single pond and on a single night.…”
Section: Discussionsupporting
confidence: 92%
“…With autochthonous proportional abundance greater in the littoral zone and allochthonous proportional abundance greater in the riparian, there is evidence that short-wavelength LED lighting creates both dispersal barriers and an asymmetrical vacuum effect wherein aquatic emergent insects are more readily pulled from their habitat of origin than are terrestrial invertebrates. A recent study examining distance thresholds on adult aquatic insects [48] found that a majority of Trichoptera were captured much closer to the aquatic-riparian border than other taxa, such as Ephemeroptera, concurring with our findings that the capture versus vacuum effect varies among taxa. This taxa-specific response suggests a degree of predictability of communities and ecosystems to ALAN, and also highlights the context dependency of our work, performed in a single pond and on a single night.…”
Section: Discussionsupporting
confidence: 92%
“…While the impacts of ALAN on insects have usually been studied using terrestrial insects, data are presently accumulating on the effects of light pollution on aquatic insects that have flying adult stages; Ephemeroptera and Trichoptera were caught by traps that were located near portable LED lights in an effort to mimic realistic ALAN conditions at different distances from riparian areas (Carannante et al, 2021). While the Ephemeroptera and Trichoptera catches were greater in traps set near rivers, the Diptera were trapped at all distances from the river.…”
Section: Effect Of Alan On Nocturnal Insectsmentioning
confidence: 99%
“…While the Ephemeroptera and Trichoptera catches were greater in traps set near rivers, the Diptera were trapped at all distances from the river. Carannante et al (2021) recommended that LED lighting should be placed at 40-60 m from riverbanks to prevent the attraction of adult aquatic flying insects. The larvae of aquatic insects were also attracted to mid-regions of the spectrum, and the Ephemeroptera larvae did not exhibit phototaxis towards blue light (Kühne et al, 2021).…”
Section: Effect Of Alan On Nocturnal Insectsmentioning
confidence: 99%
“…As many insects are known to be attracted to, and find shorter wavelengths (UV, blue) more visible (Briscoe & Chittka, 2001), the selection of an LED that emits less blue light may reduce the attraction of flying freshwater insects to outdoor lights. Despite a global trend towards LED conversions, there is little published research on the effects of LEDs on freshwater insects, with the exception of research on attraction distance thresholds (Blumenstein et al, 2018; Carannante et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on varying insect taxa found significant declines in flying insect abundance attracted to lights over short dispersal or attraction distances. In these, the specific distance where the greatest decline in abundance occurred was variable and likely to have been taxa‐dependent: for example, in the distance range 0–20 m for Trichoptera (Collier & Smith, 1997), 0–15 m for Lepidoptera (Merckx & Slade, 2014; Truxa & Fiedler, 2012), 0–10 m for Trichoptera and Ephemeroptera (Blumenstein et al, 2018; Carannante et al, 2021), and 0–3 m for Trichoptera, Diptera and Ephemeroptera (Perkin et al, 2014). Therefore, increasing the distance that lights are set back from a waterway is expected to reduce freshwater insect attraction to artificial lights.…”
Section: Introductionmentioning
confidence: 99%